Status Specific Tailoring of Sperm Behavior in an External Fertilizer - Egeland, Torvald B.; Rudolfsen, Geir; Nordeide, Jarle T.; Folstad, Ivar (Frontiers in Ecology and Evolution, 2016)
Why dominant males experiencing intense sperm competition sometimes show low investments in sperm production is not always obvious. One well-documented example is that of the external fertilizing teleost, the Arctic charr (Salvelinus alpinus), where individuals becoming dominant reduce sperm production and sperm swimming speed in water compared to subordinates. Here, we report how ovarian fluid differentially influences sperm velocity of dominant and subordinate male Arctic charr. That is, sperm from dominant males increase their velocity in water diluted ovarian fluid compared to that observed in water, while sperm from subordinates, on the other hand, decrease velocity in ovarian fluid compared to that observed in water. Thus, subordinates, who invest more resources in their sperm and usually show the highest sperm velocity in water, have lower gains from their investment than dominant males when sperm are swimming in ovarian fluid. In sum, our result suggests that ovarian fluid increase sperm velocity more in dominant males than in subordinate males. Although this finding could partly be caused by cryptic female choice exerted by the ovarian fluid for sperm from dominant males, an alternative and more parsimonious explanation is that sperm from dominant males may simply be better designed for swimming in ovarian fluid compared to sperm from subordinate males. Thus, sperm production in the two reproductive roles seems to be adaptively tailored to different external environments.